Peran Guru dalam Meningkatkan Minat dan Pemahaman Siswapada Materi Pembelajaran Fiqih di MTs Sirnamiskin Kota Bandung - Ilham Abdurrahman; Nissa Nurrohmah; Alifia Reza; Muhsin (At-Tadris: Journal of Islamic Education, 2025)
Many students find fiqh lessons quite difficult and boring, especially when the teaching method is still one-way and uninteresting. This is where the role of teachers is crucial, not only as a deliverer of material, but also as a facilitator who is able to create a lively, enjoyable, and relevant learning atmosphere for everyday life. This study aims to understand how teachers' roles in increasing students' interest and understanding of fiqh lessons at MTS SIRNAMISKIN. This study also used a qualitative approach, with data collection techniques including observation, interviews, and documentation. The findings indicate that teachers who apply varied learning methods such as group discussions, case studies, and the use of audiovisual media successfully arouse students' interest in learning. Furthermore, when teachers provide real-life examples that are close to students' daily lives, their understanding of fiqh material becomes deeper and more meaningful.